2015
DOI: 10.3141/2523-15
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Deficient Pavement Sections by Means of an Improved Acceleration-Based Metric

Abstract: Transportation agencies devote significant resources toward the collection of highly detailed and accurate pavement roughness data by using profiler vans to support pavement maintenance decisions. However, these agencies often cannot afford to measure roughness annually for the whole pavement network. This study introduced an improved acceleration-based metric, an index normalized by vehicle operating speed, to be used on a regular basis to screen pavement segments that are likely to be deficient; then a profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 5 publications
(7 reference statements)
0
5
0
1
Order By: Relevance
“…Recentemente, com vistas à redução de custos e possibilidade de coleta de dados a partir de processos colaborativos (crowdsourcing), passaram a ser utilizados dispositivos móveis para a avaliação da irregularidade longitudinal de pavimentos, em termos de IRI (International Roughness Index). Alguns buscam o cálculo direto do índice a partir dos sinais de aceleração verticais fornecidos por esses aparelhos [4,7,8], enquanto outros analisam a correlação entre esse índice e os dados de aceleração [9,10,11,12,13,14,15,16].…”
Section: Resultsunclassified
“…Recentemente, com vistas à redução de custos e possibilidade de coleta de dados a partir de processos colaborativos (crowdsourcing), passaram a ser utilizados dispositivos móveis para a avaliação da irregularidade longitudinal de pavimentos, em termos de IRI (International Roughness Index). Alguns buscam o cálculo direto do índice a partir dos sinais de aceleração verticais fornecidos por esses aparelhos [4,7,8], enquanto outros analisam a correlação entre esse índice e os dados de aceleração [9,10,11,12,13,14,15,16].…”
Section: Resultsunclassified
“…A number of studies have demonstrated that the measured vertical acceleration is related to vehicle speed (Douangphachanh and Oneyama 2014;Zeng 2014;Du et al 2014). To better understand the influence of vehicle speed on simulated Grms, one type of vehicle was modeled [i.e., a D-class sedan (DSD)] travelling at speeds ranging from 30 to 100 km=h on four roads of very good (IRI ¼ 1) to poor road condition (IRI ¼ 7.3) (Table 4).…”
Section: Effect Of Vehicle Speedmentioning
confidence: 99%
“…The results showed that smartphones measured road roughness with an acceptable accuracy when compared with an inertial profiler [8]. Zeng et al (2015) determined that road roughness depends on a normalized acceleration index. The data were collected by mounting two tablets on a vehicle dashboard.…”
Section: Introductionmentioning
confidence: 98%
“…Data were captured on the acceleration in three dimensions, the GPS coordinates, and the speed. This revealed that the recommended index could define road surface deficiencies with a high precision (between 80 and 93 percent) [9]. Hanson et al (2014) made an effort to correlate road roughness between a smartphone and a conventional profiler.…”
Section: Introductionmentioning
confidence: 99%